LOS IMPUESTOS RECAUDADOS POR EL SERVICIO DE RENTAS INTERNAS, PERÍODO 2005-2014, Y SU INCIDENCIA EN LOS INGRESOS DEL SECTOR PÚBLICO NO FINANCIERO ECUATORIANO - Cruz Casas, Johanna Maribel (2016)
During the last years, many changes have been experienced regarding to taxing in Ecuador. Thus, new taxes have been created, imposition percentages have been modified, and taxable rates have been reformed by issuing laws, regulations and resolutions; this has contributed to increase the amount of collected taxes by the Internal Revenue Service, at the time, it has increased the national income, specifically, the income of Non-Financial Public sector. The tax revenues are one of the most important and representative incomes in Ecuador. Despite of this antecedent, the current level of tax collection is not the ideal. On the other hand, there are no studies which analyze the correlation between the tax revenues and the incomes of Non-Financial Public Sector; so a gap in this line has been created and in order to cover it, this research has been carried out which title is “Taxes collected by the Internal Revenue System, during the period 2005-2014, and its incidence on the incomes of Non-Financial Public Sector”. Its main purpose is to determine the taxes collected by the Internal Revenue Service during the period 2005-2014, by using a descriptive study to establish the incidence on the incomes of the Ecuadorian Non-Financial Public Sector. The participants were over 18 years-old citizens who pay taxes and the employees at IRS. The scope of this research was national. The scientific method was used through its variations: inductive, deductive and analytic. The investigative techniques applied were the bibliographic and the interview. After the research was carried out, it can be concluded that during the period 2005-2014, the taxes collected by the IRS have represented just 31,35% in annual average from the income of the Non-Financial Public Sector, showing a positive and high correlation of 0.98 between both variables (tax collection and incomes of Non-Financial Public Sector).